Piano Learning Of Blind Children In Extracurricular Program At SLB-A Karya Murni Medan - Tarigan, Praise De Lord; Hirza, Herna (Universitas Negeri Medan, 2019)
The research aims to know about learning piano of blind children in the extracurricular program at Karya Murni Medan. This research located in Jalan Karya Wisata, Medan Johor. This research was using collective data technique with a qualitative descriptive method to describe piano learning of blind children in SLB-A Karya Murni Medan. The time of the study was conducted from February 2019 “ June 2019. Based on this research, it was found that in the learning piano for blind children was very different and difficult besides the learning piano for normal children, that™s why the teacher must be more patient in giving the learning.